Legal Design in Sustainable Antitrust - Roman Inderst; Stefan Thomas (ZBW – Leibniz Information Centre for Economics, 2022)
We lay out a roadmap for how the legislator could create a framework of "sustainability corridors" that would allow to rely on the ancillary restraints doctrine to make antitrust law more accommodating of sustainability considerations. We show how this avoids the pitfalls of a multi-goals approach, under which it would be left to antitrust authorities and courts to reconcile sustainability and competition objectives, while out-of-market benefits (externalities), that would escape even a broad consumer welfare approach, can still be accounted for. Our proposal sets out specific requirements for such sustainability corridors that ensure that the ensuing antitrust assessment is governed by a strict and quantifiable indispensability test. Specifically, we discuss three such instances: specific sustainability obligations placed on individual firms, which may however require collective actions; specific mandates that are targeted at the respective industry rather than individual firms; and policy objectives that are not targeted at individual firms or industries but provide a metric for the measurement of sustainability benefits (e.g., by way of conducting an abatement cost analysis).
Keywords: D4; 330; sustainability; ancillary restraints doctrine